2019
DOI: 10.1016/j.ijid.2019.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Impact evaluation of a Critical Pathway for patients with Clostridium difficile infection: A pre-post analysis in a Third Level Referral Center

Abstract: Background: Clostridium Difficile Infections (CDIs) have been increasing both in incidence and in severity, representing a big public health concern. Aim: The aim of this study was to evaluate the impact of a recently implemented Critical Pathway (CP) focused on patients with CDI in an Italian Teaching Hospital. Methods: The CP implementation consisted of intervention aimed to faster diagnosis and appropriateness in admission and discharge point of care; activation of a multidisciplinary team; staff training; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The pre-/post-RMM approach of this study was appropriate to evaluate the immediate impact of short-term programmes (e.g. 12-18 months) such as RMMs [5,6]. Limited improvements were observed between the study periods, suggesting that the aRMMs had a low impact; however, most RMMs, including contraindications, precautions of use and liver monitoring, were already in place in November 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-/post-RMM approach of this study was appropriate to evaluate the immediate impact of short-term programmes (e.g. 12-18 months) such as RMMs [5,6]. Limited improvements were observed between the study periods, suggesting that the aRMMs had a low impact; however, most RMMs, including contraindications, precautions of use and liver monitoring, were already in place in November 2014.…”
Section: Discussionmentioning
confidence: 99%
“…This study design is aligned with the guideline on good pharmacovigilance practices (GVP) module XVI, where a medical chart abstraction is considered as a valuable option to assess clinical knowledge and prescribing behavior and is preferred to surveys or self‐reported data. The pre‐post retrospective study design, widely used among similar PASS and DUS, allows for showing the immediate impact of short‐term programs such as RMMs . A review of 29 studies in the European Union electronic Register of Post‐Authorization Studies found that only four studies used retrospective medical files review—others were surveys—and only 10 studies were conducted within a 12–18‐month timeframe after RMM implementation .…”
Section: Discussionmentioning
confidence: 99%
“…The pre-post retrospective study design, widely used among similar PASS and DUS, [9][10][11][12][13][14] allows for showing the immediate impact of short-term programs such as RMMs. 15,16 A review of 29 studies in the European Union electronic Register of Post-Authorization Studies found that only four studies used retrospective medical files review-others were surveys-and only 10 studies were conducted within a 12-18-month timeframe after RMM implementation. 17 The main strength of this PASS remains its conclusiveness on the effectiveness of RMMs on the prescribing of ivabradine since EU marketing authorization.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology replicated one already applied by the team to another clinical setting. 20 For Delphi's first round, experts were asked to express their degree of agreement on a Likert scale from 1 to 3 (with 1 corresponding to the lowest-"Not relevant" and 3 to the highest-"Relevant"), with the set of the statements formulated for each question, with regard to the four criteria described above.…”
Section: Methodsmentioning
confidence: 99%